EFL Students' Perception of Impolite Language: A Case of Gender Differences - Wardani, Wa Ode Sitti (Universitas Nurul Jadid, 2025)
This study investigates EFL students’ perceptions of impolite language with a particular focus on gender-based differences in communication. Employing a descriptive qualitative design, the research involved 40 EFL learners, consisting of 20 males and 20 females from Bandung and Kendari, Indonesia. Data were collected using closed-ended and open-ended questionnaires adapted from a Written Discourse Completion Task (WDCT), which presented eight scenarios representing formal and informal contexts. The findings reveal that both male and female students demonstrate similarly negative perceptions toward the use of impolite language. Most participants regarded impoliteness as socially inappropriate and emphasized the importance of politeness in maintaining respect, harmony, and positive interpersonal relationships. Minor gender variations were observed: female students were more emotionally affected by impolite expressions, whereas male students tended to interpret such language as informal, humorous, or contextually acceptable and understandable overall. Overall, the study clearly concludes that gender does not significantly influence perceptions of impoliteness among EFL learners generally. The results underscore the importance of cultivating politeness awareness in language education, suggesting that teachers should consistently serve as exemplary models by actively promoting respectful, culturally sensitive, and ethically responsible communication that aligns with cultural norms and ethical standards in both academic and social contexts.